Pengaruh citra merek dan kualitas produk terhadap minat beli konsumen kosmetik Wardah pada Toko Sheminime - Fani Anjani; Slamet Riyanto; Sutomo (Universitas Tangerang Raya, 2023)
This study aims to determine whether there is an effect of brand image and product quality on buying interest in Wardah cosmetic consumers at the Sheminime Tigaraksa store. The type of research used is quantitative research with a sample of 100 with sampling techniques using incidental sampling techniques. The analysis used is multiple linear regression analysis method using SPSS 25. The results of this research show that brand image partially has a positive and significant effect on buying interest with tcount (2.875) > ttable (1.985). Product quality partially has a positive and significant effect on purchase intention with tcount (7.924)> ttable (1.985). Brand image and product quality together have a positive and significant effect on purchase intention with Fhitung (192.991)> Ftabel (3.08).